Single-island home range use by four female Peary caribou, Bathurst Island, Canadian High Arctic, 1993-94 - Miller, Frank L.; Barry, Samuel J. (Rangifer, 2003)
Spatial and temporal use of seasonal, and collectively, annual ranges by four female Peary caribou (Rangifer taran-dus pearyi) was investigated using satellite telemetry. Knowledge of how caribou use space allows a better understanding of their demands on those ranges and enhances evaluation of associated environmental stressors. The study took place during an environmentally favorable caribou-year with high reproduction and calf survival and low (none detected) 1+ yr-old mortality, 1 August 1993 to 31 July 1994, Bathurst Island, south-central Queen Elizabeth Islands, Canadian High Arctic. All four females exhibited a pattern of single-island seasonal, and collectively, annual range use. Estimates of the maximum area encompassed by each individual during the course of the annual-cycle varied from 1735 to 2844 km2 (mean±SE = 2284±250 km2). Although, there was 46% spatial overlap among individual ranges, temporal isolation resulted in the four individuals maintaining seasonal ranges distinctly separate from each other. This collective area encompassed 4970 km2 and equaled about 31% and 18% of Bathurst Island and the Bathurst Island complex, respectively. Individual wintering areas formed a relatively small portion of each individual's annual range (mean±SE=71±17 km2): 24 km2, 158 days of occupation,
Keywords: caribou; Bathurst Island; home range; displacement vs. travel; distributions; Rangifer tarandus pearyi; movements; satellite telemetry locations